Crystal structure of bis{4-bromo-2-[(carbamimidamidoimino)methyl]phenolato-κ3N,N′,O}cobalt(III) nitrate dimethylformamide monosolvate - Elena A. Buvaylo; Katerina A. Kasyanova; Olga Yu. Vassilyeva; Brian W. Skelton (Acta Crystallographica Section E: Crystallographic Communications, 2016)
The title compound, [Co(C8H8BrN4O)2]NO3·C3H7NO, is formed of discrete [CoL2]+ cations, nitrate anions and dimethylformamide (DMF) molecules of crystallization. The cation has no crystallographically imposed symmetry. The ligand molecules are deprotonated at the phenol O atom and octahedrally coordinate the CoIII atoms through the azomethine N and phenolate O atoms in a mer configuration. The deprotonated ligand molecules adopt an almost planar conformation. In the crystal lattice, the cations are arranged in layers in the ab plane divided by the nitrate anions and solvent molecules. No π–π stacking is observed. All of the amine H atoms are involved in hydrogen bonding to nitrate, DMF or ligand O atoms or to one of the Br atoms, forming two-dimensional networks parallel to (100).